Genome-wide identification and expression analysis of SBP-box gene family reveal their involvement in hormone response and abiotic stresses in Chrysanthemum nankingense - Ziwei Li; Yujia Yang; Bin Chen; Bin Xia; Hongyao Li; Yunwei Zhou; Miao He (PeerJ, 2022)
SQUAMOSA promoter-binding-protein (SBP)-box family proteins are a class of plant-specific transcription factors, and widely regulate the development of floral and leaf morphology in plant growth and involve in environment and hormone signal response. In this study, we isolated and identified 21 non-redundant SBP-box genes in Chrysanthemum nankingense with bioinformatics analysis. Sequence alignments of 21 CnSBP proteins discovered a highly conserved SBP domain including two zinc finger-like structures and a nuclear localization signal region. According to the amino acid sequence alignments, 67 SBP-box genes from Arabidopsis thaliana, rice, Artemisia annua and C. nankingense were clustered into eight groups, and the motif and gene structure analysis also sustained this classification. The gene evolution analysis indicated the CnSBP genes experienced a duplication event about 10 million years ago (Mya), and the CnSBP and AtSPL genes occurred a divergence at 24 Mya. Transcriptome data provided valuable information for tissue-specific expression profiles of the CnSBPs, which highly expressed in floral tissues and differentially expressed in leaf, root and stem organs. Quantitative Real-time Polymerase Chain Reaction data showed expression patterns of the CnSBPs under exogenous hormone and abiotic stress treatments, separately abscisic acid, salicylic acid, gibberellin A3, methyl jasmonate and ethylene spraying as well as salt and drought stresses, indicating that the candidate CnSBP genes showed differentiated spatiotemporal expression patterns in response to hormone and abiotic stresses. Our study provides a systematic genome-wide analysis of the SBP-box gene family in C. nankingense. In general, it provides a fundamental theoretical basis that SBP-box genes may regulate the resistance of stress physiology in chrysanthemum via exogenous hormone pathways.